Reflecting on the evolution of tourist and recreational development in the FinnishRussian borderland - Stepanova, Svetlana V. (Rozwój Regionalny i Polityka Regionalna, 2019)
This article examines the development of tourism and recreation in the Finnish-Russian borderland as a new promising area of regional growth. The unique natural, historical, and cultural resources, and a favourable economic and geographical position are basic prerequisites for the development of tourism in the region. Historically, the barriers of state borders hampered the development of tourism; and tourism was seen as an activity bringing no economic benefits to regions since most Soviet citizens travelled as beneficiaries of social programs. As a result of the socioeconomic transformations in the Russian Federation, the openness of border regions under the influence of integration process taking place in the world community facilitates tourist mobility between neighbouring countries. The article describes an approach that considers the border regions of Northwest Russia as attractive destinations for tourists from neighboring countries. The author presents an approach that interprets cross-border tourist routes as an instrument for the conservation, reproduction, and promotion of natural, cultural, and historical heritage and as a means to boost business activities in border regions. The author analyses statistical and analytical data and does the content analysis of regional strategies for tourism and socioeconomic development. The article explores the practices of tourism and recreation development in a historical perspective and examines the effect of barrier and contact functions of state borders on tourism. The article identifies factors hindering tourism development and suggests measures to stimulate tourism as a regional economic activity.